Recodification of corruption crime provisions in the national criminal code - Tri Indriati; Nurfatiha Rizkiah; Muh Nur Mazrur Mazhar (Integritas: Jurnal Antikorupsi, 2024)
Corruption crimes, as contained in the National Criminal Code, are controversially regulated. These have lower sanctions compared to the previous provisions in the Corruption Eradication Law. Indonesia's Corruption Perception Index has decreased since 2022, from a score of 38/100 to 34/100. Additionally, there have been several convictions wherein punishment involved imprisonment below the minimum timespan. This implies that the purpose of punishment, which is to eradicate corruption, has not been achieved. This research was conducted to determine the issue of light sanctions for defendants in corruption cases. It analyzes the Theory of Legal Truth and the Cost-Benefit Model Theory, as it pertains to the impact of recodifying corruption provisions into the National Criminal Code. This research employs prescriptive analysis, assessing what should be in the applicable legal regulations. It regards legal theory and the application of positive law to analyze a case study and address the research question. This research determines that light sentences allocated to corruption defendants reflect the low sanctions provisions, triggering increases in corruption cases. Moreover, the imposition of lower sanctions in the National Criminal Code risks encouraging an increase in corruption crimes in the future. This creates serious concerns regarding the effectiveness of law enforcement in deterring potential perpetrators against corruption.